Niemeyer Virus: A New Mimivirus Group A Isolate Harboring a Set of Duplicated Aminoacyl-tRNA Synthetase Genes - Boratto, Paulo V. M.; Arantes, Thalita S.; Silva, Lorena C. F.; Assis, Felipe L.; Kroon, Erna G.; La Scola, Bernard; Abrahão, Jônatas S. (Frontiers in Microbiology, 2015)
It is well recognized that gene duplication/acquisition is a key factor for molecular evolution, being directly related to the emergence of new genetic variants. The importance of such phenomena can also be expanded to the viral world, with impacts on viral fitness and environmental adaptations. In this work we describe the isolation and characterization of Niemeyer virus, a new mimivirus isolate obtained from water samples of an urban lake in Brazil. Genomic data showed that Niemeyer harbors duplicated copies of three of its four aminoacyl-tRNA synthetase genes (cysteinyl, methionyl and tyrosyl RS). Gene expression analysis showed that such duplications allowed significantly increased expression of methionyl and tyrosyl aaRS mRNA by Niemeyer in comparison to APMV. Remarkably, phylogenetic data revealed that Niemeyer duplicated gene pairs are different, each one clustering with a different group of mimivirus strains. Taken together, our results raise new questions about the origins and selective pressures involving events of aaRS gain and loss among mimiviruses.